2016
DOI: 10.1002/jlcr.3424
|View full text |Cite
|
Sign up to set email alerts
|

Biological evaluation of new [18F]F‐labeled synthetic amino acid derivatives as oncologic radiotracers

Abstract: The present study evaluated the tumoral uptake of the novel synthetic amino acid positron emission tomography (PET) tracers (S)-2-amino-3-(4-([(18) F]fluoromethyl)-1H-1,2,3-triazol-1-yl)propanoic acid (AMC-101), (S)-2-amino-4-(4-([(18) F]fluoromethyl)-1H-1,2,3-triazol-1-yl)butanoic acid (AMC-102), and (S)-2-amino-5-(4-([(18) F]fluoromethyl)-1H-1,2,3-triazol-1-yl)pentanoic acid (AMC-103), all of which are (S)-2-amino-(4-([(18) F]fluoromethyl)-1H-1,2,3-triazol-1-yl)alkyl acids. In vitro cellular uptake was inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…In these scenarios, the CuAAC ligation can be particularly useful, as azide- or alkyne-bearing prosthetic groups can be radiolabeled and then clicked to vectors in a one-pot two-step schema. This approach is especially popular in the synthesis of 18 F-labeled agents, as evidenced by a large library of 18 F-labeled clickable groups that includes [ 18 F]­fluorobenzyl azides, , azide- and alkyne-modified [ 18 F]­fluoropyridines, [ 18 F]­fluoroalkyl azides, , [ 18 F]­fluorocarbohydrate azides, ,, [ 18 F]­fluoropolyoxyethylene azides, ,, 3-[ 18 F]­fluoropropyne, 5-[ 18 F]­fluoropentyne, , ethynyl-4-[ 18 F]­fluorobenzene, and [ 18 F]­AMBF 3 . , In one recent example, Wang et al reported the synthesis of a modular scaffold for combined near-infrared (NIR) fluorescence and PET imaging via the CuAAC-mediated modification of an azide-bearing NIR dye with an 18 F-labeled alkyne . The work of Walker et al provides a particularly fine example of the pros and cons of a two-step, CuAAC-driven approach to radiofluorination (Figure ).…”
Section: The Copper-catalyzed Azide–alkyne Cycloadditionmentioning
confidence: 99%
“…In these scenarios, the CuAAC ligation can be particularly useful, as azide- or alkyne-bearing prosthetic groups can be radiolabeled and then clicked to vectors in a one-pot two-step schema. This approach is especially popular in the synthesis of 18 F-labeled agents, as evidenced by a large library of 18 F-labeled clickable groups that includes [ 18 F]­fluorobenzyl azides, , azide- and alkyne-modified [ 18 F]­fluoropyridines, [ 18 F]­fluoroalkyl azides, , [ 18 F]­fluorocarbohydrate azides, ,, [ 18 F]­fluoropolyoxyethylene azides, ,, 3-[ 18 F]­fluoropropyne, 5-[ 18 F]­fluoropentyne, , ethynyl-4-[ 18 F]­fluorobenzene, and [ 18 F]­AMBF 3 . , In one recent example, Wang et al reported the synthesis of a modular scaffold for combined near-infrared (NIR) fluorescence and PET imaging via the CuAAC-mediated modification of an azide-bearing NIR dye with an 18 F-labeled alkyne . The work of Walker et al provides a particularly fine example of the pros and cons of a two-step, CuAAC-driven approach to radiofluorination (Figure ).…”
Section: The Copper-catalyzed Azide–alkyne Cycloadditionmentioning
confidence: 99%
“…18 F-Radiolabelled amino acids can be valuable agents for the diagnosis and visualization of cancer. Tumour cells have high biosynthetic demand [149], and one way that they can secure an increased supply of biosynthetic building blocks is by upregulating amino acid transporter proteins [150,151]. Thus, 18 F-radiolabelled amino acids often selectively accumulate in tumours, where their presence can be detected by positron emission tomography.…”
Section: F-labelled Amino Acids and Peptides As Pet Tracersmentioning
confidence: 99%
“…This important radiotracer is particularly valuable for the imaging of brain cancers as the amino acid transporter proteins mentioned above enable this tracer to efficiently cross the blood-brain barrier [150,[152][153][154]. Prosthetic groups for the radiolabelling of several other amino acids besides tyrosine [155][156][157] have also been developed, taking advantage of the reactivity of the side chains of serine (41) [158], threonine (42) [158], tryptophan (43) [159], cysteine (44) [160,161], and ornithine (45) [151,162] (Figure 3a). Certain more elaborate prosthetic groups afford the alternative possibility of late-stage fluorination through 18 F/ 19 F isotopic exchange (e.g., 46-47) [163,164].…”
Section: F-labelled Amino Acids and Peptides As Pet Tracersmentioning
confidence: 99%